Effects of culture enrichment and light source on growth of Spirulina platensis in modified sago effluent - Tan, Zi Ni (Universiti Malaysia Sarawak, UNIMAS, 2008)
Spirulina platensis, which is photosynthetic algae, can serve as food supplement to human, feed to animal and used as a coloring compound in industries. The growth of Spirulina in modified sago effluent (MSE) is observed with optical density (560nm) every 2 days and biomass is determined according to standard calibration curve (OD vs DCW). In the effects of light, biomass produced in MSE under artificial light was higher compare to natural light with 268.84 mg/L and 214.85 mg/L respectively after 8 days of cultivation. Amendments on MSE showed that culture added with nitrate produced highest biomass at 447.13 mg/L, with bicarbonate at 354.89 mg/L and with phosphate at 322.27 mg/L with the same period under artificial light. Biomass produced from Zarrouk’s medium under artificial light (as control, 8 days of cultivation) was 219.91 mg/L and maximum biomass was achieved in this medium was at 596.18 mg/L on the 16 days of cultivation. The maximum biomass of Spirulina plantensis achieved in MSE under artificial light was 284.59 mg/L (4 days of cultivation) and at 214.85 mg/L under natural light (8 days of cultivation). Spirulina platensis was successfully cultivated in modified sago effluent and the best parameters for the growth was addition of nitrate on MSE under artificial light with maximum biomass at 519.69 mg/L on 10 days of cultivation. Hence, MSE can be used beneficially without disposing into rivers thus minimizing environmental pollution.